Medical treatment of digestive bleeding - Kaufmann, Pedro (Cirugía del Uruguay, 1974)
Patients suffering from digestive hemorrhage should be cared for by a medico-surgical team composed of gastroenterologist, surgeon and radiologist. After reinstatement of volemia, by venous catheterism, initial diagnostic exploration should be performed at once so as to determine what is bleeding. In hemorrhages of esophago-gastro-duodenal origin pan-endoscopy should be performed at once, complemented if necessary by selective arteriography and conventionál gastro-duodenal examination. lf urgency surgery is not indicated, a schedule for medical treatment should be established, consisting of hourly cold milk diet, non-absorbable antiacids and drugs. Clinícal, nursing and laboratory control are important during this _period. Grave low digestive hemorrhages should first receive medica! treatment. After urgency endoscopy for the purpose of diagnosis, specific medica! treatment should be set in accordance with etiology. Finally case material, consisting of 585 digestive hemorrhages is described; 469 were not operated and evolution was good in 60 % of cases.